PENGARUH INFLASI DAN TINGKAT PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Zaki; Mutira Sani (Universitas Sumatera Barat, 2020)
The purpose of this study was to determine the effect of inflation and the unemploymentrate on economic growth in West Sumatra partially and simultaneously. This research is aquantitative study with secondary data in the 2013-2018 observation period. Secondary datacollection uses the documentation method for inflation, unemployment and economic growthreport data from BI and BPS. The independent variable in this study is inflation and theunemployment rate, while the dependent variable is economic growth. Data analysis used ismultiple linear regression using SPSS version 16.00, the test results partially indicate thatinflation, the unemployment rate has a significant effect on economic growth. And the results ofthe tests simultaneously show inflation and the unemployment rate have a significant effect oneconomic growth, with a significance of 97.8% and the remaining 2.2% influenced by othervariables.